Menadione modulates adipogenic differentiation by inhibition of PI3K/Akt pathway in 3T3-L1 cells - Iglesias González, Pablo Andrés (2018)
We have previously demonstrated that menadione-induced oxidative stress significantly diminishes adipogenesis and is able to dephosphorylate and inactivate phosphatidylinositol 3-kinase (PI3K)/Akt pathway in 3T3-L1 cells (SAIB 2017). To investigate this unexpected behavior of this adipogenic key pathway against oxidative stress, we mimicked menadione effect by studying adipogenic differentiation in the presence of LY294002, a well known PI3K inhibitor. In the absence of menadione, we found that PI3K inhibition drastically decreased adipogenesis. At a molecular level, the expression of peroxisome proliferator activated receptor gamma (PPAR gamma), the master regulator of adipogenesis, was also found to be decreased. To investigate if PI3K/Akt pathway was responsible of menadione-caused adipogenesis inhibition, we used insulin in the presence of menadione as a PI3K gain-of-function strategy, both being present during the whole differentiation process. These experiments showed that insulin was sufficient to rescue PPAR gamma expression, without altering cell viability. These results show that PI3K/Akt is a key pathway in the antiadipogenic effect of menadione on 3T3-L1 cells.